Patient experience: Driving outcomes at the heart of healthcare - Jason Wolf (The Beryl Institute, 2016)
There is no longer a question that patient experience matters in healthcare today. It matters for those that are cared for and served and matters to all those working each and every day to provide the best in care at all touch points across the healthcare continuum. With this recognition, there too needs to be a change in mindset about patient experience itself. When addressing the topic of patient experience, the conversation is about something much broader than the “experience of care”, as identified in the triple aim. The idea of experience reflects our biggest opportunity in healthcare, where experience encompasses quality, safety and service moments, is impacted by cost and the implications of accessibility and affordability, is influenced by the health of communities and populations and by both private and public health decisions that have systemic implications. A focus on experience at the broadest sense leads to the achievement of the four outcomes leaders aspire to in varying combinations in healthcare organizations around the world: clinical outcomes, financial outcomes, consumer loyalty, and community reputation. With the rapid growth in research, a diverse and expanding global community, and a shared commitment to outcomes, patient experience has now claimed its place at the heart of healthcare.